Effect of natural dye combination and pH extraction on the performance of dye-sensitized photovoltaics solar cell - Indri Wasa Estiningtyas; Nita Kusumawati; Pirim Setiarso; Supari Muslim; Nunik Tri Rahayu; Riska Nur Safitri; Nafisatus Zakiyah; Fadlurachman Faizal Fachrirakarsie (International Journal of Renewable Energy Development, 2023)
Dyes are significant components in Dye Sensitized Solar Cell (DSSC) performance because they act as photosensitizers. Natural dye-based DSSC system fabrication innovations continue to be produced in an effort to improve DSSC performance efficiency. In this study, a DSSC system was developed using double components of natural dyes as natural photosensitizers to enhance DSSC efficiency. This method of making natural dye-based DSSC uses a combination of dye extracts from two different dye sources that have the potential as natural photosensitizers in DSSC. The research aims to investigate the impact of the combined use of two natural dyes and pH variations on DSSC performance. DSSC performance measurements encompass the short-circuit current (Isc), open-circuit voltage (Voc), and DSSC efficiency parameters. The obtained results indicate efficiency values for dyes (a) sappan wood/ethanol and turmeric/methanol; (b) turmeric/methanol and beetroot/ethanol; and (c) beetroot/ethanol and turmeric/distilled water. At neutral pH, the efficiency values are 2.09%, 2.10%, and 2.19%, respectively. Meanwhile, at acidic pH of 2.59%; 2.39%; and 2.71%. Notably, the dye efficiency values at acidic pH surpass those found at neutral pH conditions. The highest efficiency is observed in the combination of dye (c) beetroot/ethanol and turmeric/distilled water with efficiency reaching 2.71% at acidic pH.